The synergistic effects of circuit training and diet on weight loss, body fat percentage, and BMI in obese Indonesian females: a randomized controlled trial - Rahim, Ali Muthahhari; Nasrulloh, Ahmad (Indonesian Journal of Research in Physical Education, Sport, and Health, 2025)
Background: Despite the popularity of circuit training and dietary interventions, their combined effects on obese Southeast Asian populations remain underexplored.  Objective: This study aims to examine the effects of circuit training (using free weights and body weight) and dietary interventions (low-calorie diet and intermittent fasting using the OCD method), as well as their interaction, on weight loss, body fat percentage, and body mass index in obese individuals. Methods: This type of research is an experiment using a 2 x 2 factorial design. This experimental study used four groups that received different treatments, namely the provision of circuit training with free weight and low-calorie diet, the provision of circuit training without tools (body weight) with a low-calorie diet, circuit training and OCD diet, and the provision of circuit training without tools (body weight) with the OCD diet. The place of data collection was carried out at the fitness Healty and Sport Center (HSC UNY). The population in this study is HSC UNY fitness members, and a sample of 20 obese females (aged 20–30) underwent a 6-week intervention with 16 training sessions was taken using the purposive sampling technique. The researcher conducted three initial measurement variables (pretest) of each HSC UNY fitness center member, namely weight, fat percentage, and BMI. Result: The results of the study showed that significant weight loss (7.48 kg, p=0.00), but no significant changes in fat percentage (p=0.302) or BMI (p=0.841). Conclusion: The study concluded that circuit training using free weights combined with the OCD diet was the most effective method for weight loss, though the reduction in fat percentage and BMI was not statistically significant. This combination is recommended for fitness programs targeting weight loss in similar demographics, though longer studies are needed to assess fat reduction. Future research should explore longer intervention periods, larger sample sizes, and additional variables such as metabolic rate and adherence levels to better understand the effectiveness of different training and dietary strategies. This combination is recommended for fitness programs targeting weight loss in similar demographics.